A new species of Cirolana Leach, 1818 (Isopoda, Cymothoidea, Cirolanidae) from Brazilian coast - Ricardo J.C. Paiva; Jesser F. Souza-Filho (Nauplius)
A new species of Cirolana is described from the Northeast Brazilian coast based on the material previously recorded as Cirolana palifrons and some other material misidentified as C. parva. The new species, C. lemoscastroi sp. nov., belongs to a group of species within the genus that have two dorsal longitudinal carinae on the pleotelson. A key to all Cirolana species recorded from Brazil is provided.